Real-world impact of Information Systems: the effect of seemingly small design choices - Ableitner, Liliane; Tiefenbeck, Verena; Hosseini, Sabiölla; Schöb, Samuel; Fridgen, Gilbert; Staake, Thorsten (Workshop on Information Technology and Systems (WITS), 2017)
Information system (IS) have not only become indispensable in professional contexts, but can also serve as a platform for data-based interventions targeting issues for humanity. Providing individuals with concrete feedback on their current behavior has been shown to foster sustainable behavior. So far, research on the real-world impact and underlying mechanisms of such IS-enabled interventions is scarce. In a randomized controlled field experiment with 1,423 participants, we systematically test the effect of different intervention strategies regarding their impact on energy consumption and user experience. We find a conservation effect of over 18% for the best treatment. In particular, the results suggest that small, seemingly harmless variations of IS design choices regarding numerical, normative, or emotional feedback can considerably affect behavioral outcomes (energy use). Potential explanations of observed behavior are given based on theories from psychology. The study delivers design implications for innovative IS artifacts that highlight the importance and necessity of taking cognitive processes into account. <br